Evaluation of relationships between dogs and owners: the turkish translation, reliability and validity study of cat/dog owner relationship scale (c/dors) - Ufuk Kaya; Dogukan Ozen; Murat Onur Yazlik; Selim Kosem; İsmayil Safa Gurcan (Eurasian Journal of Veterinary Sciences)
Aim: The aim of this study was to translate the cat/dog owner relationship scale (C/DORS), which can be used to assess the quality of relationships between dogs and their owners, into Turkish and to evaluate relationship quality across different demographic variables in Turkey. Materials and Methods: An expert team translated the cat/dog owner relationship scale (C/DORS) from its original language of English into Turkish. Information was collected from dog owners who volunteered to participate in the study via a scale. The dog owners' gender, educational status, and financial level were also collected. The validity and reliability of the scale were assessed using Cronbach's alpha and factor analysis. Results: The initial statistical analyses revealed that factor analysis could be used on the scale (Bartlett?s sphericity test, p<0,001) and that the sample size was adequate (KMO test=0,619). The total variance explained by the scale that has three subscales as perceived emotional closeness, pet-owner interaction and perceived cost was found to be 43,90%. The Cronbach's alpha coefficient of the scale was found to be 0.844. It was observed that the subscale scores of the scale were at similar levels in terms of gender (p>0,05) and income statue (p>0,05). Perceived cost subscale score was statistically significant in terms of educational status (p<0,05). Conclusion: It is thought that this scale, that has been adapted into Turkish and whose validity-reliability has been determined, is the first scale that can measure dog-owner relationships in Turkey. In addition, this study will encourage the examination of pet-human relationships in Turkey through with scale development and adaptation studies.